Kontribusi Doa Nabi Ibrahim Terhadap Perkembangan Perekonomian Arab Pra Islam – Pasca Islam (Studi Pemikiran Tafsir Ma’alim Al-Tanzil Karya Al-Baghawi) - Abdul Basid; Nur Faizin; Zhafira Qotrun Nada; Savira Manzilina (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2022)
Imam Al-Baghawi, an expert in commentary, hadith, and fiqh who lived during the Abbasid caliphate and grew up from the Shafi'iyah school. He was always consistent in his studies and also composed many books, one of which was Mu'allimat tanzil, explaining the science of interpretation and involving the words of the Qur'an. One of them is QS. Al-Baqarah verse 126 contains the prayer of the Prophet Ibrahim. To Allah, to provide security for the country where his family and other people live there is a clear proof of his concern for the country and surrounding residents, including the environment and welfare in the city of Mecca. The prayer of Prophet Ibrahim in surah al-Baqarah verse 126, according to Hamka, this verse ordered the Prophet Muhammad. Back to the Quraysh that it was their ancestors who started the land of Mecca where they lived, namely Prophet Ibrahim.